Infrared laser desorption of hydroquinone from a water-ethanol liquid beam - Otten, D.; Trevitt, B.; Nichols, G.; Metha, G.; Buntine, Mark (American Chemical Society, 2003)
We have investigated the 1.9-mum IR desorption of hydroquinone in a water/ethanol liquid beam under relatively high desorption laser fluences (1316 and 2632 mJ cm(-2) pulse(-1)). The appearance of the IR desorption/UV ionization TOF mass spectrum of hydroquinone (HQ) is interpreted in terms of dissociation of solvated HQ clusters during the ionization event. The maximum in the hydroquinone desorption velocity distribution is 300 ms-1, and the translational temperature of the desorbed species is approximately 1500 K. We see no evidence for an acoustic compression - ejection mechanism, suggesting that such a process is operative at desorption laser fluences lower than employed here. Our results suggest a general mechanism for the high-powered IR desorption from a liquid beam whereby desorbed species are ejected into the vacuum possessing considerable translational energy but remain internally cool.